On the Transfer of Inertial Particles Under Sharp Accelerations of the Medium - Ingel’, L. Kh (Journal of engineering physics and thermophysics, 2025)
The nonlinear problem on the acceleration of a massive particle picked up by fast flow in a gravity field has been investigated analytically. This problem is of interest, in particular, in connection with hazardous convective phenomena in the lower atmosphere (squally gusts of wind, tornadoes). Heavy particles/objects transferred by intense winds represent one basic factor of hazard associated with such phenomena. Relevant theoretical problems are complicated by the linear dependence of the hydrodynamic resistance on the particle velocity with respect to the medium and have been investigated by numerical methods as a rule. In the work, consideration has been given to the analytical model enabling us to establish certain general regularities of acceleration of particles in nonstationary flows. Emphasis was placed upon situations with short-duration pulse changes in the medium′s velocity.